Delayed atorvastatin delivery promotes recovery after experimental spinal cord injury - Samuel C. Buchl; Ha Neui Kim; Benjamin Hur; Whitney L. Simon; Monica R. Langley; Jaeyun Sung; Isobel A. Scarisbrick (Neurotherapeutics)
Spinal cord injury (SCI) significantly alters gene expression, potentially impeding functional recovery. This study investigated the effects of atorvastatin, a widely prescribed cholesterol-lowering drug, on gene expression and functional recovery in a chronic murine SCI model. Female C57BL/6J mice underwent moderate 0.25 ​mm lateral compression SCI and received daily atorvastatin (10 ​mg/kg) or vehicle-only injections from two weeks post-injury for four weeks. Sensorimotor functions were assessed using the Basso Mouse Scale (BMS), its subscore, and the inclined plane test. RNA sequencing of spinal cord tissues identified robust transcriptomic changes from SCI and a smaller subset from atorvastatin treatment. Atorvastatin enhanced sensorimotor recovery within two weeks of treatment initiation, with effects persisting to the experimental endpoint. Pathway analysis showed atorvastatin enriched neural regeneration processes including Fatty Acid Transport, Axon Guidance, and the Endocannabinoid Developing Neuron Pathway; improved mitochondrial function via increased TCA Cycle II and reduced Mitochondrial Dysfunction; and decreased Inhibition of Matrix Metalloproteases. Key gene drivers included Fabp7, Unc5c, Rest, and Klf4. Together, these results indicate atorvastatin's potential in chronic SCI recovery, especially where already indicated for cardiovascular protection.